Optimizing lonafarnib treatment for the management of chronic delta hepatitis: The LOWR HDV‐1 study. Issue 4 (19th February 2018) - Yurdaydin, Cihan; Keskin, Onur; Kalkan, Çağdaş; Karakaya, Fatih; Çalişkan, Aysun; Karatayli, Ersin; Karatayli, Senem; Bozdayi, A. Mithat; Koh, Christopher; Heller, Theo; Idilman, Ramazan; Glenn, Jeffrey S.
Abstract : In a proof‐of‐concept (POC) study, the oral prenylation inhibitor, lonafarnib (LNF), decreased hepatitis D virus (HDV) RNA during 4 weeks of treatment. Here, we explored optimal LNF regimens. Fifteen patients (five groups; 3 per group) completed dosing as follows: (1) LNF 200 mg twice‐daily (BID; 12 weeks); (2) LNF 300 mg BID (12 weeks); (3) LNF 100 mg thrice‐daily (5 weeks); (4) LNF 100 mg BID + pegylated interferon alfa (PEG‐IFNα) 180 μg once‐weekly (QW; 8 weeks); and (5) LNF 100 mg BID + ritonavir (RTV) 100 mg once‐daily (QD; 8 weeks). Tolerability and efficacy were assessed. Higher LNF monotherapy doses had greater decreases in HDV viral load than achieved in the original POC study. However, this was associated with increased gastrointestinal adverse events. Addition of RTV 100 mg QD to a LNF 100 mg BID regimen yielded better antiviral responses than LNF 300 mg BID monotherapy and with less side effects. A similar improvement was observed with LNF 100 mg BID + PEG‐IFNα 180 μg QW. Two of 6 patients who received 12 weeks of LNF experienced transient posttreatment alanine aminotransferase (ALT) increases resulting in HDV‐RNA negativity and ALT normalization. Conclusion : The cytochrome P450 3A4 inhibitor, RTV, allows a lower LNF dose to be used while achieving higher levels of postabsorption LNF, yielding better antiviral responses and tolerability. In addition, combining LNF with PEG‐IFNα achieved more substantial and rapid HDV‐RNA reduction, compared to historical responses with PEG‐IFNα alone. Twelve weeks of LNF can result in posttreatment HDV‐RNA negativity in some patients, which we speculate results from restoring favorable immune responses. These results support further development of LNF with RTV boosting and exploration of the combination of LNF with PEG‐IFN. (Hepatology 2018;67:1224‐1236)